Another brick in the wall: fifth millennium BC earthen-walled architecture on the Channel shores. (6th August 2015) - Laporte, Luc; Bizien-Jaglin, Catherine; Wattez, Julia; Guyodo, Jean-Noël; Barreau, Jean-Baptiste; Bernard, Yann; Aoustin, David; Guitton, Véronique; Hamon, Gwenaelle; Jallot, Luc; Lucquin, Alexandre; March, Ramiro; et al.
Abstract